Kebiasaan Makan Ikan dan Trofik Level Sepanjang Perairan Pantai Kabupaten Barru - Muh. Hatta; Sri Mulyani (DEDIKASI, 2019)
The purpose of this study is to determine the trophic structure of pelagic fish around Barru coastal waters.So that by knowing the structure of the tropic level it can be determined the ideal number of populations that shouldbe captured at all trophic levels so that small and large pelagic fish resources can maximally and sustainably beutilized. The benefits of this research with a trophic level approach can be made a model of fisheries managementpolicy in a region of the Makassar Strait in supporting the accelerated economic development program in theSulawesi Economic Corridor. The research method is taking data on environmental parameters and predation at eachtrophic level including fish through observing fish gastric contents. Identification results of gastric contents indicatethat anchovy and tembang fish are plankton (planktivore) eaters because only Phytoplankton and zooplankton canbe found in their intestine. Pepetek fish, fish float and mackerel eat plankton and several types of larvae of small fishand crustaceans so that they are classified as omnivores. Selar fish classify as carnivorous fish because in itsintestine found various types of small fish, shrimp, and various other animals and not obtained plankton as its mainfood item. Anchovy and tembang fish which are included as planktivore, have a greater percentage of phytoplanktonin their intestines compared to zooplankton.